Modelling Kiesler's Endless Theatre: approaches to paradata for heritage visualization. Issue 1 (3rd April 2021) - Hann, Rachel
ABSTRACT: This article is an outcome of my investigations into the use of computer-based 3D visualization as a research methodology. Frederick Kiesler's unrealized Endless Theatre (1916–26) project is employed as a case study for articulating 'paradata' in heritage visualization. This builds upon the principles of knowledge transparency outlined within the London Charter (2008). My overall objective for this article is to argue paradata as a critical framework for reading and designing heritage visualization. This is particularly focused on the procedural insights from a modeller's perspective and practical techniques for 'thick depiction', including a proposal for 'paradata maps'. To evidence these positions, the article details two contextual findings on the Endless Theatre project – concerning the principles of 'continuous movement' and 'audience seating' – that emerged through the visualization process itself. The article concludes with an appraisal of paradata as a critical framework and computer-based 3D visualization as a historiographic method that, it argues, has offered new insights into Kiesler's unrealized theatre project.